2018
DOI: 10.5056/jnm18010
|View full text |Cite
|
Sign up to set email alerts
|

Improving High-resolution Impedance Manometry Using Novel Viscous and Super-viscous Substrates in the Supine and Upright Positions: A Pilot Study

Abstract: Background/AimsSwallows with viscous or solid boluses in different body positions alter esophageal manometry patterns. Limitations of previous studies include lack of standardized viscous substrates and the need for chewing prior to swallowing solid boluses. We hypothesize that high-resolution impedance manometry (HRiM) using standardized viscous and super-viscous swallows in supine and upright positions improves sensitivity for detecting esophageal motility abnormalities when compared with traditional saline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This is likely caused by the patient's dilated left ventricle, which was identified by chest X‐ray, CT scans, and vascular artifacts in the distal esophagus in the HRiM plots (Figure 2A‐D). As part of an IRB‐approved research protocol, we also performed 5 swallows of a unique viscous solution 8 in both supine and upright positions, which showed similar results with saline swallows, that is, normal peristalsis and poor bolus transit (Figure 2B,D). Because he is not a robust surgical candidate with cardiomyopathy (ejection fraction of 30%), chronic kidney disease, and other comorbidities, he is being managed with dietary modifications and is currently able to keep his weight stable.…”
Section: Case Reportmentioning
confidence: 88%
“…This is likely caused by the patient's dilated left ventricle, which was identified by chest X‐ray, CT scans, and vascular artifacts in the distal esophagus in the HRiM plots (Figure 2A‐D). As part of an IRB‐approved research protocol, we also performed 5 swallows of a unique viscous solution 8 in both supine and upright positions, which showed similar results with saline swallows, that is, normal peristalsis and poor bolus transit (Figure 2B,D). Because he is not a robust surgical candidate with cardiomyopathy (ejection fraction of 30%), chronic kidney disease, and other comorbidities, he is being managed with dietary modifications and is currently able to keep his weight stable.…”
Section: Case Reportmentioning
confidence: 88%
“…35 On the other hand, in a study of healthy volunteers, viscous swallows identified more incomplete bolus clearance measured on impedance, compared with saline swallows. 34 In a study assessing PROs, metrics and findings obtained using solid or viscous swallows on manometry did not correlate with either the presence of symptoms or their severity. 36 Therefore, the clinical significance of manometric findings obtained using viscous and solid swallows and their correlation with symptoms and clinical outcomes need to be further defined for routine clinical use.…”
Section: Solid Swallows During Hrmmentioning
confidence: 92%
“…Viscous and solid swallows were found to be associated with a higher IRP, longer EGJ relaxation duration, shorter transition zone, slower contractile front velocity, more vigorous DCI, and higher intrabolus pressure. 30,[32][33][34] Different sets of normative values have also been developed for solid swallows in both upright and supine positions from these studies of healthy controls. 32 Despite the increased diagnostic yield of abnormal motility pattern with viscous or solid swallows, the correlation between these findings and either BT or clinical symptoms remains conflicted.…”
Section: Solid Swallows During Hrmmentioning
confidence: 99%
“…Limited available studies suggest that semi-solid and solid swallows increase sensitivity to identify an abnormality in patients presenting with dysphagia. [81][82][83][84] However, normative values for manometric parameters with semi-solid and solid swallows are limited. Similarly, a standardized test meal may improve diagnostic sensitivity of HRM and has the potential to alter the diagnosis beyond what was found with standard water swallows.…”
Section: A Test Meal Helps To Detect Esophageal Motility Disorders Beyond Water Swallowsmentioning
confidence: 99%